Peran Diplomasi Maritim Indonesia sebagai Poros Maritim Dunia - Afifah Winda Ramadhani; Muhammad Imran Hanafi; Mulawarman Mulawarman; Dea Rizky Amalia (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This paper discusses the role of Indonesia's maritime diplomacy in realizing its vision as the Global Maritime Fulcrum (Poros Maritim Dunia - PMD). Indonesia’s maritime diplomacy focuses on strengthening maritime security, enhancing maritime infrastructure connectivity, sustainable marine resource management, and promoting maritime culture. Through active participation in international forums such as IORA and cooperation with G20 countries, Indonesia aims to strengthen its strategic position as a global maritime trade hub. This study highlights how maritime diplomacy supports the achievement of the five pillars of PMD, solidifying Indonesia's role in the Indo-Pacific region and enhancing the country's global influence.